Housing conditions in social housing stock vs. marginalisation risk – evidence from Poland - Rataj, Zuzanna; Suszynska, Katarzyna (Research Papers in Economics and Finance, 2021)
Low-income households in the Polish public housing stock sometimes encounter the risk of housing exclusion, yet this experience is relatively more frequent among the tenants of council flats. The aim of this paper is to present the results of research on housing standards in the public housing stock in Poland. Pursuant to Polish law, social housing is part of public housing assistance (Przymeński 2016), addressed to very-low- and low-income households which are not capable of satisfying their housing needs on their own. The paper uses desk research, statistical data analysis and questionnaire interviews with dwellers of council flats in Poland. Furthermore, the achievements of international housing policy are taken into account. The results show that the standard in the public stock, especially in council flats, in Poland is poor and hinders low-income households in addressing their hous- ing needs. Small areas of dwellings, overcrowding, low quality of building materials are all identified as significant determinants increasing the risk of housing exclusion in council flats.